PENGARUH OPASITAS LABA, ASIMETRI INFORMASI, DAN KEINFORMATIFAN LABA TERHADAP BIAYA EKUITAS DI PERUSAHAAN MANUFAKTUR - Melinda Malau; Etty Murwaningsari; Sekar Mayangsari; Titik Aryati (Jurnal Akuntansi Trisakti, 2019)
This study aims to examine and analyze whether earnings opacity, information asymmetry, earnings informativeness have effect to the cost of equity. The method used in this study is panel regression analysis. The sample used in the study was 900 observations consisting of 500 observations in Indonesia and 400 observations in the Philippines using data from manufacturing companies for the period 2013-2017. Cost of equity is measured by a three-factor model. Earnings aggressiveness, loss avoidance, and income smoothing as a proxy for earnings opacity. Information asymmetry is measured by the bid-ask spread. Earnings informativeness are measured by discretionary accruals. The result shows that earnings opacity has a significant positive effect on the cost of equity. Information asymmetry has a significant positive effect on the cost of equity. Earnings informativeness have a significant negative effect on cost of equity.